The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1097/01.ypg.0000218620.50386.f1
|View full text |Cite
|
Sign up to set email alerts
|

Association of catecholamine-O-methyltransferase and 5-HTTLPR genotype with eating disorder-related behavior and attitudes in females with eating disorders

Abstract: We found associations between the COMT and the 5-HTTLPR polymorphisms and specific clinical, behavioral and attitudinal traits of eating disorders. These polymorphisms may predispose their carriers to exhibit certain symptoms of eating disorders or confer a general risk for more severe forms of these disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 23 publications
1
26
0
1
Order By: Relevance
“…A few studies examining the association between EDs and 5-HTTLPR were excluded because they were not in case-control design. [36][37][38] The proportions of alleles and genotypes of control samples in all included studies were consistent with the Hardy-Weinberg equilibrium. First, the percentage of the S allele was compared between patients with AN and controls in seven studies (see Fig.…”
Section: Resultsmentioning
confidence: 74%
“…A few studies examining the association between EDs and 5-HTTLPR were excluded because they were not in case-control design. [36][37][38] The proportions of alleles and genotypes of control samples in all included studies were consistent with the Hardy-Weinberg equilibrium. First, the percentage of the S allele was compared between patients with AN and controls in seven studies (see Fig.…”
Section: Resultsmentioning
confidence: 74%
“…Of these, eight studies included AN samples [24][25][26][27][28][29][30][31] and seven included BN samples. 22,24,27,28,[32][33][34] Three additional studies have been included, two being performed on samples of eating disorder patients (AN and BN considered together) 23,35 and one being performed on a sample of BED patients. 36 The methodological quality of the included studies according to the Newcastle-Ottawa scale 12 is shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…27 Random effects indicated a mild association (Z 5 2.14, p 5 .03), the between-study heterogeneity remaining significant (v 2 5 33.78, df 5 13, p 5 .001, I 2 5 62%). In a third sensitivity analysis we removed all the studies plausibly contributing to between-study heterogeneity: the studies with virtual controls, 28,31,34,35 the study on BED 36 and the study performed on Japanese population. 27 Random effects indicated no association (Z 5 1.25, p 5 .21), the between-study heterogeneity remaining significant (v 2 5 23.07, df 5 8, p 5 .003, I 2 5 65%).…”
Section: Prevalence Of 5-httlpr S-containing Genotype Versus L/l Genomentioning
confidence: 99%
See 1 more Smart Citation
“…[82][83][84] Interestingly, shared genetic variance between negative emotionality and both body dissatisfaction and weight preoccupation were limited. 67 Drive for thinness is associated with potentially biologically plausible mechanisms, where elevated levels are associated with carriers of the deletion polymorphism of the serotonin transporter promoter 5-HTTLPR 85 and has been a valuable covariate in linkage analyses. 86 In women recovered from bulimia-type AN, [ 18 F]altanserin binding potential and drive for thinness were negatively correlated in several cortical regions, suggesting that altered 5-HT neuronal system activity persisted.…”
Section: Cognitive Featuresmentioning
confidence: 99%